Sinergi Deep Learning dan Kearifan Lokal untuk Pengembangan Literasi Bahasa dan Sastra Indonesia pada Anak Sekolah Dasar - Yoma Hatima (FKIP UNSULTRA, 2025)
The development of artificial intelligence technology, particularly deep learning, opens up new opportunities for developing Indonesian language and literature literacy at the elementary school level. Furthermore, local wisdom, as part of the nation's cultural identity, holds significant potential for strengthening literacy learning that is contextual, meaningful, and relevant to children's lives. This article presents a literature review on the synergy between deep learning and local wisdom in developing Indonesian language and literature literacy in elementary school children. Deep learning plays a role in providing technology-based learning media, such as interactive applications, automatic text analysis, and reading recommendation systems that can be tailored to children's abilities. Meanwhile, local wisdom provides content rich in cultural, moral, and social values, enabling children not only to acquire literacy skills but also to foster a sense of national identity and character. The review shows that the integration of these two aspects can create an adaptive, creative, and inclusive literacy ecosystem. Literacy is understood not only as reading and writing skills but also as a means of strengthening imagination, critical thinking, and cross-cultural understanding. This study emphasizes the need for a collaborative approach between deep learning technology and local wisdom to improve the quality of Indonesian language and literature learning in elementary schools, while simultaneously preparing a literate, character-driven, and globally competitive golden generation.